An essential introduction to Maya character rigging - Cabrera, Cheryl (Routledge, 2008)
Discover the concepts and techniques required to rig engaging CG character models with Maya in this unique book and DVD package. The stunning color images show just what you can achieve, and the detailed step-by-step tutorials show exactly how to achieve them. Every technique and tip is backed up with practical tutorials, using the models, student work and tutorial assets on the companion DVD to offer a crash course in this vital skill. With Cheryl Cabrera you'll learn about:Designing your first Biped Character; Creating your firs.